An open source, server-side framework for analytical web mapping andits application to health - Moncrieff, Simon; West, Geoff; Cosford, James; Mullan, Narelle; Jardine, Andrew (Taylor & Francis, 2014)
In this paper, we detail the design and the implementation of an open source, server-side web mapping framework for the analysis of health data. The framework forms part of a larger project, the goal of which is to provide an analytical web geographical information system (GIS) that enables health experts to analyse spatial aspects of health data. The aim of the framework is to provide a method for the dynamic and flexible spatial visualisation of health data to facilitate data exploration and analysis. Consequently, a dynamic thematic web mapping technique, an extension to the Open Geospatial Consortium (OGC) web map service standard, was developed. The technique combines a data query, processing technique and styling methodology on the fly to generate a thematic map. The resulting thematic map represents a virtual map layer that enables a user to rapidly visually summarise properties of a data-set. A test web interface was developed to assess the efficacy of the web mapping technique. As the dynamic web mapping method builds on existing OGC web mapping standards, it can be readily integrated with the existing lightweight slippy map web clients and virtual globes.